The Meaning of Disgust: A Refutation. (July 2014) - Strohminger, Nina
Recently, McGinn (2011) has proposed a new theory of disgust. This theory makes empirical claims as to the history and function of disgust, yet does not take into account contemporary scientific research on the subject. This essay evaluates his theory for its merits as an account of disgust, and as a piece of scholarship more generally, and finds it lacking.